Project-Based Learning Models Approach In Improving Arabic Speaking Ability - Abdul Muid; Muhammad Fadhlan; Rasidin Rasidin; Muhammad Dasrul Jabir (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2022)
The learning process is closely related to the elements that influence it, such as approaches, methods, and techniques. The purpose of this study is to describe objectively (a) the application of learning Arabic speaking skills using a project-based learning model in the maharah kalam course for students of the Jambi University Arabic Language Education Study Program, (b) the results of improving Arabic speaking skills by applying the project model. based PBA student at Jambi University. This research uses a classroom action design with three cycles. The study results indicate that the application of learning Arabic with a project-based learning model can improve speaking Arabic for students of the Jambi University Arabic Language Education Study Program.